Mechanisms of anguilliform locomotion in fishes studied using simple three-dimensional physical models. (5th July 2016) - Lim, Jeanette L; Lauder, George V
Abstract: Physical models enable researchers to systematically examine complex and dynamic mechanisms of underwater locomotion in ways that would be challenging with freely swimming animals. Previous research on undulatory locomotion, for example, has used rectangular flexible panels that are effectively two-dimensional as proxies for the propulsive surfaces of swimming fishes, but these bear little resemblance to the bodies of elongate eel-like swimming animals. In this paper we use a polyurethane rod (round cross-section) and bar (square cross-section) to represent the body of a swimming Pacific hagfish ( Eptatretus stoutii ). We actuated the rod and bar in both heave and pitch using a mechanical controller to generate a propulsive wave at frequencies between 0.5 and 2.5 Hz. We present data on (1) how kinematic swimming patterns change with driving frequency in these elongate fish-like models, (2) the thrust-generating capability of these simple models, (3) how forces and work done during propulsion compare between cross-sectional shapes, (4) the wake flow patterns in these swimming models using particle image velocimetry. We also contrast kinematic and hydrodynamic patterns produced by bar and rod models to comparable new experimental data on kinematics and wake flow patterns from freely swimming hagfish. Increasing the driving frequency of bar and rod models reduced trailing edge amplitude and wavelength, and above 2 Hz a nodal point appeared in the kinematic wave. Above 1 Hz, both the rod and bar generated net thrust, with the work per cycle reaching a minimum at 1.5 Hz, and the bar always requiring more work per cycle than the rod. Wake flow patterns generated by the swimming rod and bar included clearly visible lateral jets, but not the caudolaterally directed flows seen in the wakes from freely swimming hagfish.